Physical Condition Profile of Badminton Athletes Pre-Porprov 2025 in Banyumas Regency - Indarto, Asyidika Vito; Prabowo, Trisnar Adi; Abdillah, Muh. Jamil; Galeko, Jaka Patama; Leksono, Kuat (Journal Sport Science Indonesia, 2025)
The purpose of this study is to analyze the physical condition profile of badminton athletes in the 2025 Banyumas Regency Pre Porprov through physical tests. This study is a quantitative study with a cross-sectional survey. The sample was 17 athletes aged 18 to 21 years with total sampling. The instruments for data collection used were 30-meter sprint (speed), 60 second sit-ups (abdominal muscles), 60 second push-ups (arm muscles), 30 second handball throwing and catching (coordination), Vertical Jump (leg muscle power), Illinois Agility Run (agility), Multistage Fitness Test (endurance). The results are that speed in male athletes is in the good category and in female athletes is in the poor and very poor category, abdominal muscles in male and female athletes are the same in the poor category, arm muscles in male athletes are in the sufficient category and in female athletes are in the good category, coordination in male athletes is in the poor and very poor category and in female athletes is in the very poor category, leg muscle power in male athletes is in the sufficient category and in female athletes is in the good category, agility in male athletes and female athletes is both in the good category. In the sufficient category, endurance in male athletes is in the very good category and in female athletes is in the good category. In conclusion, many factors influence physical conditions such as environment, level of motivation, recovery process, nutrition, and physical activity. It is hoped that future research can expand the research sample and data collection methods so that they can analyze, compare and study physical conditions in depth.